Proteomic approach toward personalized sarcoma treatment: Lessons from prognostic biomarker discovery in gastrointestinal stromal tumor. Issue 1 (22nd January 2013) - Kondo, Tadashi; Suehara, Yoshiyuki; Kikuta, Kazutaka; Kubota, Daisuke; Tajima, Takashi; Mukaihara, Kenta; Ichikawa, Hiroshi; Kawai, Akira; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> Sarcomas range from curable tumors to those causing death via metastasis and recurrence. Thus, there is an urgent need for biomarker identification in order to assess the degree of malignancy, predict prognosis, and evaluate possible therapies. Various proteomic approaches and different clinical materials have been used to this end, and candidate biomarkers have been reported for the different types of sarcomas. However, the sample size used in these biomarker studies was generally insufficient, and thus far, no biomarker has been proved useful in clinics. Given that sarcomas are rare, biomarker validation in this setting is more challenging than in other malignancies. In gastrointestinal stromal tumor, adjuvant therapy has proven to be effective. However, only 40% patients experience metastasis after curative surgery alone, and the rest of the patients may not need adjuvant therapy. Using a proteomic approach, we identified pfetin (potassium channel tetramerization domain containing 12, KCTD 12) as a novel prognostic biomarker for sarcoma, and immunohistochemically confirmed its clinical usefulness by a multiinstitutional validation study. Here, we describe our experience and discuss the critical points in the discovery of this biomarker.